Minimally Invasive Distal Metatarsal Osteotomy for Juvenile Hallux Valgus Correction: A Retrospective Radiographic Evaluation - Sara Mateen DPM; Michael A. Thomas DPM, MS, AACFAS; Yumna Siddiqui DPM; Jim R. McWilliam MD; Noman Siddiqui DPM (Foot & Ankle Orthopaedics, 2023)
Category: Bunion; Midfoot/Forefoot Introduction/Purpose: The minimally invasive distal metatarsal osteotomy (MIDMO) is an increasingly popular technique for hallux valgus (HV) correction in the adult population. In juveniles, however, the use of minimally invasive methods to surgically resolve HV remains a comparatively new and under-reported concept. The primary objectives of this retrospective review are to provide radiographic findings of pediatric patients who underwent surgical correction of HV via the minimally invasive distal metatarsal osteotomy (MIDMO). Secondary objectives are the utilization of the mechanical axis of the first metatarsal to measure pre- and postoperative radiographic outcomes and time to osseous consolidation. Methods: A multi-center retrospective review was performed of two institution system’s records was conducted for consecutive patients who underwent surgical correction for HV between January 2012 and June 2022. Patients were included if they underwent HV correction using MIDMO, were aged < 18 years, had ≥ 3 months of clinical and radiographic follow-up, and had radiographs on file of both pre- and postoperative anteroposterior (AP) and lateral views. The first IMA (anatomic and mechanical axes), hallux abductus angle (HAA), distal metatarsal articular angle (DMAA), and tibial sesamoid position (TSP) were measured in pre- and postoperative AP and lateral views. A paired sample t-test was used to compare pre- and postoperative absolute radiographic measured angles. Results were considered statistically significant at the 5% (P < 0.05) level. Results: Forty-two feet amongst 30 patients met the inclusion criteria. Twenty seven were female (90%) and 3 of whom were male (10%). Temporary pin fixation (23.8%) or screw fixation (76.2%). Mean patient age was 15.2 years. Mean follow-up was 13.7 months. Mean time to osseous consolidation was 6.7 weeks. A statistically significant reduction was noted in all the radiographic values of every angle measured from preoperative to postoperative. The mean first anatomic IMA changed from 14.52° to 3.53° postoperatively and the first mechanical IMA changed from 14.24° to 4.64° postoperatively. The mean HAA was reduced from 32.98° to 12.83° postoperatively, the mean DMAA shifted from 12.40° to 2.93° postoperatively, and the mean TSP was revised from 3.60° preoperatively to 1.07° postoperatively. Conclusion: This is the first retrospective North American radiographic review in the known literature that evaluates short-term results of juvenile HV correction utilizing the MIDMO. Our results support the conclusion that the MIDMO is an effective method for pediatric patients with HV and provides statistically significant radiographic correction. Additionally, our results support the versatility of the mechanical axis in evaluating pre- and postoperative radiographic outcomes of the first IMA. We recommend future larger efforts with greater patient populations and longer follow-up times for further investigation.